Adolescence Students’ Critical Thinking Skills in The Context of Christian Education - Yosef Patandung (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The purpose of this study is to assess the critical thinking skills of adolescence students at junior high schools in Rantepao, particularly in the context of Christian education. This study employed a quantitative design research and using proportionate stratified random sampling method to select the sample. There are 66 students became the sample of this study. Data were collected through questionnaire that assessed the students' critical thinking skills based on the critical thinking indicators. The collected data then analyzed by using descriptive statistics calculation related to the variables of critical thinking skills. Result of this study found that adolescnence students at Junior High School in Rantepao have only a fair level of critical thinking skills in the context of Christian Education. This study highlights the need for improving students' critical thinking skills in the context of Christian Education. Teacher should foster students growth by growth by focusing on their learning process and offering appropriate activities. Â